The Medical Students’ Dilemma: E-Textbook or Printed Textbook? A Cross Sectional Study from Medical Colleges in Rawalpindi Pakistan - Tariq, Naseer Alam; Saeed Awan, Bushra Ameer; Ahmed, Naseer; Amir, Mohammad Taimoor; Rasheed, Malik Abdullah; ., Muneeb; ., Yaseen (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To assess students’ perspectives of traditional learning and text books and more advanced e-learning and digital text books learning from digital and printed text. Study Design: Cross-sectional study. Place and Duration of Study: Course of six months from Jan to Jun 2022 in two Medical Colleges of Rawalpindi Pakistan. Methodology: The study was a cross-sectional study carried out over course of six months from Jan to Jun 2022 in two Medical Colleges. Participants were 300, recruited through non-probability convenience sampling technique. A questionnaire and online survey were used to obtain information about response of medical students towards e-book and printed text effecting the quality of education. The data was analyzed using SPSS software version 23.0. Results: Mean age of participants was 22±2.24 years and majority were between 21-24 years of age 212(71%) with almost equal proportions of males 140(47%) and females 160(53%) Significant association was found between gender and solid plan with traditional learning p=0.046 and more privacy of data in printed text, more reliability p=0.033.Significat association also found between age category and ease of modification of e text p=0.023, improvement in skills p=0.024 and also decrease in motivation due to technical disruption 0.034, instant feedback in e learning p=0.002. Conclusion: Mean while Medical students favored the e-learning and digital books, they didn’t over rule completely the significance of traditional learning and paperback books.